Factors Associated with Breastfeeding Self-Efficacy and COVID-19 Pandemic Anxiety in Post Partum Mothers - Yuna Trisuci Aprillia; Asyifa Robiatul Adawiyah; Kusmayra Ambarwati; Faradibha Tenrilemba (Jurnal Kesehatan Masyarakat, 2024)
Admasu, J., Egata, G., Bassore, D. G., Feleke, F. W. (2022). Effect of maternal nutrition education on early initiation and exclusive breast-feeding practices in south Ethiopia: a cluster randomised control trial. Journal of Nutritional Science, 11. https://doi.org/10.1017/JNS.2022.36American Dietetic Association. (2009). Position of the American Dietetic Association: Promoting and Supporting Breastfeeding. Journal of the American Dietetic Association, 109(11), 1926–1942. https://doi.org/10.1016/J.JADA.2009.09.018Badan Pusat Statistik. (2021). Potret Sensus Penduduk 2020 Menuju Satu Data Kependudukan Indonesia. Badan Pusat Statistik, 28. https://www.bps.go.idBareket-Bojmel, L., Shahar, G., Margalit, M. (2021). COVID-19-Related Economic Anxiety Is As High as Health Anxiety: Findings from the USA, the UK, and Israel. International Journal of Cognitive Therapy, 14(3), 566–574. https://doi.org/10.1007/S41811-020-00078-3/TABLES/2Bartle, N. C., Harvey, K. (2017). Explaining infant feeding: The role of previous personal and vicarious experience on attitudes, subjective norms, self-efficacy, and breastfeeding outcomes. British Journal of Health Psychology, 22(4), 763–785. https://doi.org/10.1111/BJHP.12254Basyouni, S. S., El Keshky, M. E. S. (2021). Job Insecurity, Work-Related Flow, and Financial Anxiety in the Midst of COVID-19 Pandemic and Economic Downturn. Frontiers in Psychology, 12, 632265. https://doi.org/10.3389/FPSYG.2021.632265/BIBTEXChen, H., Guo, J., Wang, C., Luo, F., Yu, X., Zhang, W., Li, J., Zhao, D., Xu, D., Gong, Q., Liao, J., Yang, H., Hou, W., Zhang, Y. (2020). Clinical characteristics and intrauterine vertical transmission potential of COVID-19 infection in nine pregnant women: a retrospective review of medical records. Lancet (London, England), 395(10226), 809. https://doi.org/10.1016/S0140-6736(20)30360-3Ceulemans, M., Foulon, V., Ngo, E., Panchaud, A., Winterfeld, U., Pomar, L., Lambelet, V., Cleary, B., O’Shaughnessy, F., Passier, A., Richardson, J. L., Hompes, T., Nordeng, H. (2021). Mental health status of pregnant and breastfeeding women during the COVID-19 pandemic—A multinational cross-sectional study. Acta Obstetricia et Gynecologica Scandinavica, 100(7), 1219–1229. https://doi.org/10.1111/aogs.14092 Dai, X., Dennis, C. L. (2003). Translation and validation of the breastfeeding Self-Efficacy Scale into Chinese. Journal of Midwifery and Women’s Health, 48(5), 350–356. https://doi.org/10.1016/S1526-9523(03)00283-6Dennis, C. L. (1999). Theoretical underpinnings of breastfeeding confidence: a self-efficacy framework. Journal of Human Lactation : Official Journal of International Lactation Consultant Association, 15(3), 195–201. https://doi.org/10.1177/089033449901500303Hamid, S. B. A., Zaidi, N. M. (2020). Predictors of Prenatal Breastfeeding Self-Efficacy in Malaysian Women: a Cross-Sectional Study. Jurnal Gizi Dan Pangan, 15(1), 53–62. https://doi.org/10.25182/JGP.2020.15.1.53-62Handayani, L., Md Kosnin, A., Kee Jiar, Y. (2013). Translation and Validation of Breastfeeding Self-Efficacy Scale-Short Form (BSES-SF) into Indonesian: a Pilot Study. KESMAS.Kamboj, S., Kamboj, R., Kamboj, S., Guarve, K., Dutt, R. (2020). Novel Coronavirus 2019 Outbreak: A Global Epidemic. Letters in Drug Design Discovery, 17(12), 1458–1464. https://doi.org/10.2174/1570180817999200802033916Kasmita, Nabila Tasrif, Titen Darlis Santi. (2023). Stunting in Toddlers (6-60 Months): Parenting Pattern, Mother’s Education Level, Infectious Diseases, and Breastfeeding. Jurnal Kesehatan Masyarakat, 18(4), 564–570. https://doi.org/10.15294/kemas.v18i4.41433Kemenkes RI. (2020). Pedoman Pencegahan dan Pengendalian Coronavirus Disease (COVID-19). https://covid19.kemkes.go.id/protokol-covid-19/kmk-no-hk-01-07-menkes-413-2020-ttg-pedoman-pencegahan-dan-pengendalian-covid-19Kuo, S. Y., Chen, S. R., Tzeng, Y. L. (2014). Depression and Anxiety Trajectories among Women Who Undergo an Elective Cesarean Section. PLOS ONE, 9(1), e86653. https://doi.org/10.1371/JOURNAL.PONE.0086653Larsen, J. R., Martin, M. R., Martin, J. D., Hicks, J. B., Kuhn, P. (2021). Modeling the onset of symptoms of COVID-19: Effects of SARS-CoV-2 variant. PLOS Computational Biology, 17(12), e1009629. https://doi.org/10.1371/JOURNAL.PCBI.1009629Lau, C. Y. K., Lok, K. Y. W., Tarrant, M. (2018). Breastfeeding Duration and the Theory of Planned Behavior and Breastfeeding Self-Efficacy Framework: A Systematic Review of Observational Studies. Maternal and Child Health Journal, 22(3), 327–342. https://doi.org/10.1007/S10995-018-2453-XLawrence M, G., Jane Morton, Ruth A, L., Audrey J, N., Donna, O., Richard J, S., Arthur I, E. (2005). Breastfeeding and the use of human milk. Pediatrics, 115(2), 496–506. https://doi.org/10.1542/PEDS.2004-2491Lee, H., Kim, K. E., Kim, M. Y., Park, C. G., Han, J. Y., Choi, E. J. (2021). Trajectories of depressive symptoms and anxiety during pregnancy and associations with pregnancy stress. International Journal of Environmental Research and Public Health, 18(5), 1–12. https://doi.org/10.3390/ijerph18052733Leahy-Warren, P., Mccarthy, G., Corcoran, P. (2012). First-time mothers: social support, maternal parental self-efficacy and postnatal depression. Journal of Clinical Nursing, 21(3–4), 388–397. https://doi.org/10.1111/J.1365-2702.2011.03701.XLin, R., Lu, Y., Luo, W., Zhang, B., Liu, Z., Xu, Z. (2022). Risk factors for postpartum depression in women undergoing elective cesarean section: A prospective cohort study. Frontiers in Medicine, 9, 1001855. https://doi.org/10.3389/FMED.2022.1001855/BIBTEXMcDermid, P., Sooppiyaragath, S., Craig, A., Sheel, M., Blazek, K., Talty, S., Seale, H. (2022). Psychological and financial impacts of COVID-19-related travel measures: An international cross-sectional study. PLOS ONE, 17(8), e0271894. https://doi.org/10.1371/JOURNAL.PONE.0271894Mcqueen, K. A., Dennis, C. L., Stremler, R., Norman, C. D. (2011). A pilot randomized controlled trial of a breastfeeding self-efficacy intervention with primiparous mothers. Journal of Obstetric, Gynecologic, and Neonatal Nursing : JOGNN, 40(1), 35–46. https://doi.org/10.1111/J.1552-6909.2010.01210.XMossman, M., Heaman, M., Dennis, C. L., Morris, M. (2008). The Influence of Adolescent Mothers’ Breastfeeding Confidence and Attitudes on Breastfeeding Initiation and Duration. Journal of Human Lactation, 24(3), 268–278. https://doi.org/10.1177/0890334408316075Mollard, E., Wittmaack, A. (2021). Experiences of Women Who Gave Birth in US Hospitals During the COVID-19 Pandemic. Journal of Patient Experience, 8, 1–6. https://doi.org/10.1177/2374373520981492Nicolás-López, M., González-Álvarez, P., Sala de la Concepción, A., Giralt-López, M., Lorente, B., Velasco, I., Wichner, P. S. V., Ginovart, G. (2022). Maternal mental health and breastfeeding amidst the Covid-19 pandemic: cross-sectional study in Catalonia (Spain). BMC Pregnancy and Childbirth, 22(1), 1–13. https://doi.org/10.1186/s12884-022-05036-9Noel-Weiss, J., Bassett, V., Cragg, B. (2006). Developing a Prenatal Breastfeeding Workshop to Support Maternal Breastfeeding Self‐Efficacy. Journal of Obstetric, Gynecologic Neonatal Nursing, 35(3), 349–357. https://doi.org/10.1111/J.1552-6909.2006.00053.XOtsuka, K., Dennis, C. L., Tatsuoka, H., Jimba, M. (2008). The relationship between breastfeeding self-efficacy and perceived insufficient milk among Japanese mothers. JOGNN - Journal of Obstetric, Gynecologic, and Neonatal Nursing, 37(5), 546–555. https://doi.org/10.1111/j.1552-6909.2008.00277.xProcianoy, R. S., Silveira, R. C., Manzoni, P., Sant’Anna, G. (2020). Neonatal COVID-19: little evidence and the need for more information. Jornal de Pediatria, 96(3), 269. https://doi.org/10.1016/J.JPED.2020.04.002Richard, S. A., McCormick, B. J. J., Seidman, J. C., Rasmussen, Z., Kosek, M. N., Rogawski, E. T., Petri, W., Bose, A., Mduma, E., Maciel, B. L. L., Chandyo, R. K., Bhutta, Z., Turab, A., Bessong, P., Mahfuz, M., Caulfield, L. E., Acosta, A. M., De Burga, R. R., Chavez, C. B., … Svensen, E. (2018). Relationships among Common Illness Symptoms and the Protective Effect of Breastfeeding in Early Childhood in MAL-ED: An Eight-Country Cohort Study. The American Journal of Tropical Medicine and Hygiene, 98(3), 904. https://doi.org/10.4269/AJTMH.17-0457Setiawaty, V., Kosasih, H., Mardian, Y., Ajis, E., Prasetyowati, E. B., Siswanto, Karyana, M. (2020). The Identification of First COVID-19 Cluster in Indonesia. The American Journal of Tropical Medicine and Hygiene, 103(6), 2339–2342. https://doi.org/10.4269/AJTMH.20-0554Silva, W. A. D., de Sampaio Brito, T. R., Pereira, C. R. (2022). COVID-19 anxiety scale (CAS): Development and psychometric properties. Current Psychology (New Brunswick, N.J.), 41(8), 5693–5702. https://doi.org/10.1007/S12144-020-01195-0Sinha, I. P., Harwood, R., Semple, M. G., Hawcutt, D. B., Thursfield, R., Narayan, O., Kenny, S. E., Viner, R., Hewer, S. L., Southern, K. W. (2020). COVID-19 infection in children. The Lancet. Respiratory Medicine, 8(5), 446–447. https://doi.org/10.1016/S2213-2600(20)30152-1Stepowicz, A., Wencka, B., Bieńkiewicz, J., Horzelski, W., Grzesiak, M. (2020). Stress and anxiety levels in pregnant and post-partum women during the COVID-19 pandemic. International Journal of Environmental Research and Public Health, 17(24), 1–9. https://doi.org/10.3390/ijerph17249450Sun, J., Zhu, Y., Li, Y., Li, N., Liu, T., Su, X., Dai, Z., Zhang, Y., Pan, L., Jiang, W., Zhu, W. (2020). Maternal postpartum feeding anxiety was associated with infant feeding practices: results from the mother-infant cohort study of China. BMC Pregnancy and Childbirth, 20(1), 1–9. https://doi.org/10.1186/S12884-020-03483-W/TABLES/6Victora, C. G., Bahl, R., Barros, A. J. D., França, G. V. A., Horton, S., Krasevec, J., Murch, S., Sankar, M. J., Walker, N., Rollins, N. C., Allen, K., Dharmage, S., Lodge, C., Peres, K. G., Bhandari, N., Chowdhury, R., Sinha, B., Taneja, S., Giugliani, E., … Richter, L. (2016). Breastfeeding in the 21st century: epidemiology, mechanisms, and lifelong effect. Lancet (London, England), 387(10017), 475–490. https://doi.org/10.1016/S0140-6736(15)01024-7Wayan Suriastini, Dani Alfah, Bondan Sikoki, Roni Hermoko, Listiono, Iip Umar Rifai, Dhanang Prasetya. (2020, October 8). Time to Activate Breastfeeding Behavior Change and Intervention. Survei Measurement Training Research. https://www.surveymeter.org/en/node/583World Health Organization. (2003). Global Strategy for Infant and Young Child Feeding.World Health Organization. (2020a). Breastfeeding and COVID-19. https://www.who.int/news-room/commentaries/detail/breastfeeding-and-covid-19Kemenkes RI. (2020b). Novel Coronavirus (‎2019-nCoV)‎: situation report. https://apps.who.int/iris/handle/10665/330760World Health Organization. (2020c, March 11). WHO Director-General’s opening remarks at the media briefing on COVID-19. WHO Media. https://www.who.int/director-general/speeches/detail/who-director-general-s-opening-remarks-at-the-media-briefing-on-covid-19---11-march-2020Wu, Z., McGoogan, J. M. (2020). Characteristics of and Important Lessons from the Coronavirus Disease 2019 (COVID-19) Outbreak in China: Summary of a Report of 72314 Cases from the Chinese Center for Disease Control and Prevention. JAMA - Journal of the American Medical Association, 323(13), 1239–1242. https://doi.org/10.1001/JAMA.2020.2648Yuliana, A., Zen Rahfiludin, M., Nugraheni, A. (2019). Factors Affecting Pregnant Women in Preparation of Early Breastfeeding Initiation (IMD) at Grobogan Regencys. Jurnal Kesehatan Masyarakat, 15(2), 276–285. https://doi.org/10.15294/kemas.v15i2.20547